TaSCA, an Agile Survey on Chemosensory Impairments for Self-Monitoring of COVID-19 Patients: A Pilot Study - Mucignat-Caretta, Carla; Bisiacchi, Patrizia; Marcazzan, Gian Luigi; Calistri, Arianna; Parolin, Cristina; Antonini, Angelo (Frontiers in Neurology, 2021)
Background/Objective: During the COVID-19 pandemic, smell and taste disorders emerged as key non-respiratory symptoms. Due to widespread presence of the disease and to difficult objective testing of positive persons, the use of short surveys became mandatory. Most of the existing resources are focused on smell, very few on taste or trigeminal chemosensation called chemesthesis. However, it is possible that the three submodalities are affected differently by COVID-19. Methods: We prepared a short survey (TaSCA) that can be administered at the telephone or through online resources to explore chemosensation. It is composed of 11 items on olfaction, taste and chemesthesis, in order to discriminate the three modalities. We avoided abstract terms, and the use of semiquantitative scales because older patients may be less engaged. Statistical handling included descriptive statistics, Pearson’s chi-squared test and cluster analysis. Results: The survey was completed by 83 persons (60 females and 23 males), which reported diagnosis of COVID-19 by clinical (n=7) or molecular (n=18) means, the others being non-COVID subjects. Cluster analysis depicted the existence of two groups, one containing mostly asymptomatic and one mostly symptomatic subjects. All swab-positive persons fell within this second group. Only one item, related to trigeminal temperature perception, did not discriminate between the two groups. Conclusions: These preliminary results indicate that TaSCA may be used to easily track chemosensory symptoms related to COVID-19 in an agile way, giving a picture of three different chemosensory modalities.